Socio-demographic and clinical profile of the COVID-19 positive cases among the patients attending in the fever clinic of a tertiary care hospital of Bangladesh - Arafat, Shohael Mahmud; Khan, Abed Hussain; Sharmin, Elora; Alam, Md Adnanul (Bangabandhu Sheikh Mujib Medical University Journal, 2022)
Coronavirus disease-2019 (COVID-19) caused by the virus SARS CoV 2 is a major global health concern nowadays. Bangladesh is also confronting this highly transmissible disease with an exponentially rising number of cases across the country. This study was designed to observe the socio-demographic characteristics and clinical profile of COVID-19 patients in Bangladesh is still very scanty. In this cross-sectional observational study, a total of 662 COVID-19 positive patients were enrolled following selection criteria who attended the fever clinic at BSMMU. COVID-19 was found to be more prevalent in males as the male to female ratio was 2.5:1. The mean age was 37.50 ± 12.14. Most of them belong to the 31-40 year age group. Among the patients, 41.8% were obese. DM, hypertension and bronchial asthma are the most common comorbidities. The most frequent symptoms were fever 80.8%, cough 36%, anosmia 21.8% and runny nose 1.7%. Most of the patients sought healthcare for fever 77.6 %, cough 23.3 %, dysgeusia 13.3% and anosmia 21.7 %. About 86.6 % had no history of contact with positive cases. Most of them had been BCG vaccinated previously. BSMMU J 2021; 14(4): 114-120